Convicts Life in James Tucker’s The Adventures of Ralph Rashleigh - Rina Marliana; Burhanuddin Arafah; Herawaty Herawaty (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
Convicts Life In James Tucker’s The Adventures Of Ralph Rashleigh.  Convicts transported from Britain to Australia are one of historical phenomenon. This research is aimed to describe the convicts life in the late eighteenth century to early nineteenth century in Australia as illustrated in The Adventures of Ralph Rashleigh by James Tucker. This research was a descriptive qualitative research. The data were collected by using library research and it was analyzed by applying sociological approach proposed by Swingewood (1972) who revealed three classifications of sociology of literature. In this case, the researcher focused on the classification of sociology as the mirror of age. The result of this research showed that the convicts alive harshly in Australia where the flogging was a common punishment for them